The Persique. - Persic (Troopship) ([s.l.] : H.M.T. "Persic"., 1918)
Shipboard events, humor and stories written by the soldiers.
Caption title.
"Written by and for the members of the A.I.F. on board H.M.T. 'Persic'".
Keywords: Persic (Troopship) -- Periodicals; Australia. -- Army. -- Australian Imperial Force (1914-1921) -- Anecdotes -- Periodicals